Contested Legacies : Critical Perspectives on Postwar Modern Housing - Project Muse. ([S.l.] : LEUVEN UNIVERSITY PRESS, 2023)
In the light of the current housing and environmental crisis and increasing social inequalities, there is a growing sense of urgency for architecture as a discipline to engage with the transformation in housing evident in the postwar period. Rather than conceiving this task as a technical matter, this book proposes to reassess the conditions and legacy of this large and ubiquitous housing stock. By foregrounding the mismatch between constructed cultural, social and ideological narratives and the everyday realities of residents, the contributors rediscover the value of often-overlooked modern open spaces and reconsider the technological advances that paved the way for this large-scale construction.00'Contested Legacies' advances a new notion of heritage which, rather than seeking to preserve the past, sets outs to actively transform what exists to meet current societal needs. It offers an ?atlas? of exemplary cases, each illustrating a defining yet often neglected aspect of modern postwar housing, from which present engagement and active reflection can grow, making the book an appealing read for both scholars and housing practitioners worldwide.
Description based on print version record.
Keywords: Planned communities; Apartment houses; Collectivites nouvelles -- Histoire -- 20e siecle; Planned communities -- History -- 20th century; Planned communities -- History -- 21st century; Apartment houses -- History -- 20th century; Apartment houses -- History -- 21st century; History; Electronic books